Efficiency and financial sustainability of sugarcane Farmer Cooperatives in Eswatini - Mnisi, Kuhle (Graduate School of Business (GSB), 2019)
The economy of Eswatini is heavily reliant on the production of sugarcane. However, the 2015 drought, as well as the decision by the European Union (EU) to end the quota system for sugar has had deleterious consequences for the local industry. In Eswatini, sugar imports decreased by 13.5% during the 2016/2017 financial year. Another problem is that a third of Eswatini’s sugar output originates from smallholder farmers who have experienced problems with sugarcane productivity in recent years. Therefore, to assist with future investment decisions, there is a need for continued assessment of the financial sustainability of the industry. This is imperative to enhance the productive efficiency of farmers and to improve their welfare. This study assessed the efficiency and operational sustainability of the 114 sugarcane Farmers Cooperatives (FCs) in The Kingdom of Eswatini from 2014 to 2017. The Stochastic Frontier Analysis technique, the Cobb-Douglas and the Translogarithm production functions were used to estimate technical efficiency scores. The results of the study showed that the sugarcane FCs are operationally self-sustainable, with an average technical efficiency of 83.69% (Translog) and 73.01% (Cobb-Douglas). The study identified operational sustainability, and access to grants and loans as significant contributors to improved technical efficiency. On the other hand, factors such as distance to mill, age and membership number were observed to have a negative effect on technical efficiency. Our recommendation is that government policy should focus on implementing caps on certain variables which have decreasing marginal benefit. Policy should also focus on how best to direct funding such that farmers’ operating expenses are minimised. This could be done through continual development of cost saving infrastructure to allow farmers to utilise inputs to increase efficiency.